2018
DOI: 10.5812/aapm.69275
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Constipation or Stool Consistency and Pain Severity in Patients With Chronic Pain

Abstract: BackgroundBacteria can influence a variety of gut functions. Some studies showed that stool consistency and constipation were associated with gut microbiome (GM) composition, and enterotype, dysbiosis. Growing evidence indicates the significant role of GM in the homeostatic function of the host body. The GM may regulate multiple neurochemical and neurometabolic pathways. Chronicity of the pain is actively modulated at the molecular to the network level by means of several neurotransmitters. The GM to some exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…However, no significant causal relationship was discerned between the gut microbiota and NP, TSP, or BP. The outcomes of our study align with the observations of Arai et al (2018) , who reported a noteworthy positive relationship between the severity of constipation and the intensity of pain in individuals experiencing low back pain or/and lower limb pain. Notably, the severity of constipation is known to exert a significant influence on the composition of the gut microbiota ( Zhu et al, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, no significant causal relationship was discerned between the gut microbiota and NP, TSP, or BP. The outcomes of our study align with the observations of Arai et al (2018) , who reported a noteworthy positive relationship between the severity of constipation and the intensity of pain in individuals experiencing low back pain or/and lower limb pain. Notably, the severity of constipation is known to exert a significant influence on the composition of the gut microbiota ( Zhu et al, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…One previous study found that increasing pain severity is positively associated with constipation severity. 2 This may explain the equivalent rate of constipation in both LSR and nonradicular LBP cohorts, given both conditions are inherently painful. This previously identified association underscores the importance of treating pain in patients with low back conditions with nonpharmacologic interventions rather than opioid medications, which can increase the risk of constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Although we accounted for differences between cohorts using PSM, there are numerous residual confounding variables such as those related to pain severity, 2 physical activity level, 53 socioeconomic status, stress, hormonal changes, water intake, 53 and dietary variables, which were not available in our data set. Another potential confounder is pelvic floor dysfunction, which has a limited association to LBP but strong association with constipation.…”
Section: Limitationsmentioning
confidence: 99%
“…Constipation has been positively associated with pain severity in chronic pain patients (Shiro et al 2017 ; Arai et al 2018 ; Frazzitta et al 2019 ). Authors suggest that constipation may relate to chronic pain for several reasons, such as age, gender, BMI, insufficient physical activity and excessive sedentary behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of opioid analgesics can contribute to the slow the gut transit by binding mu-opioid receptors in the enteric nervous system and thereby inhibiting motor and secretomotor neurons of the gut. Intriguingly, constipation is associated to gut microbiome dysbiosis and some authors speculate that gut dysbiosis can alter neuropeptide production in the brain and subsequently impair endogenous pain modulation (Arai et al 2018 ). Of interest, studies on subjects with chronic abdominal pain and healthy volunteers recently demonstrated that constipation and pain may influence each other, suggesting that treating one may help to alleviate the other and vice versa (Shiro et al 2017 ; Chen et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%